2000
DOI: 10.1038/modpathol.3880198
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Cardia Intestinal Metaplasia: Biopsy Follow-Up of 85 Patients

Abstract: Background: Gastric cardia intestinal metaplasia (CIM), denoted by goblet cells is common. The frequency of persistent CIM is unknown. Methods: 85 patients with CIM and follow-up endoscopies were prospectively identified during the time period of 10/6/94 -12/21/97. The presence of goblet cells was the defining feature of CIM, other metaplastic cell types were not evaluated. All 85 patients initially had biopsies that straddled the squamocolumnar junction (SCJ) showed CIM, an otherwise normal proximal stomach, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…However, not all biopsy specimens with increased chronic inflammation in mucosa from this region contain IM. In one biopsy study of the GEJ region by Goldstein et al, IM was more likely to occur in biopsies that showed high levels of chronic inflammation (60). Their data also suggested that a reduction in chronic inflammation may allow IM to revert to normal in some instances.…”
Section: Pathogenesis Of Intestinal Metaplasia In the Gastroesophageamentioning
confidence: 90%
See 1 more Smart Citation
“…However, not all biopsy specimens with increased chronic inflammation in mucosa from this region contain IM. In one biopsy study of the GEJ region by Goldstein et al, IM was more likely to occur in biopsies that showed high levels of chronic inflammation (60). Their data also suggested that a reduction in chronic inflammation may allow IM to revert to normal in some instances.…”
Section: Pathogenesis Of Intestinal Metaplasia In the Gastroesophageamentioning
confidence: 90%
“…In one study by Goldstein, a reduction in chronic inflammation in serially obtained mucosal biopsies from the GEJ in 85 patients with IM was associated with a lower prevalence rate of IM (60). However, this study was retrospective in design and limited by the potential deleterious effects of sampling error.…”
Section: Natural History and Risk Of Neoplasia Of Intestinal Metaplasmentioning
confidence: 99%
“…In 1994, Genta et al [37] were the first to report that the gastric cardia is involved in H. pylori gastritis, a finding meanwhile confirmed in a number of studies [10,12,13,[33][34][35][38][39][40][41][42][43], also in children [44]. However, there is some variability of H. pylori-infected patients who present with carditis.…”
Section: Carditis In Association With H Pylori Infectionmentioning
confidence: 79%
“…It is the combination of intestinal metaplasia in a biopsy originating in mucosa having endoscopic criteria of Barrett esophagus that allows the unequivocal diagnosis of Barrett esophagus. Whether or not intestinal metaplasia in the gastric cardia has the same significance, biology and clinical implications as in the esophagus is currently a matter of scientific debate [11], but until intestinal metaplasia is shown to have significant precancerous potential, it is important to distinguish the two.…”
Section: When Is a Diagnosis Of Barrett Esophagus Justified?mentioning
confidence: 99%